Domestic and family violence leave across Australian workplaces: Examining victim-survivor experiences of workplace supports and the importance of cultural change - Fitz-Gibbon, Kate (Journal of criminology, 2023)
There is increasing recognition across Australian industries, workplace policy makers and researchers that domestic and family violence (DFV) is a workplace issue. DFV not only impacts victim-survivors? engagement in the workforce but their work performance, job satisfaction, productivity and career progression. The economic costs of DFV to Australian workplaces are well documented; however, there is limited research capturing the workplaces? experiences of DFV victim-survivors. Reflecting increasing acknowledgement of the need for workplaces to offer supports to employees who are experiencing DFV, in October 2022, the Commonwealth Government passed legislation that introduces a 10-day paid DFV leave provision into National Employment Standards. Recognising the critical opportunity that the new legislation presents for improving DFV workplace supports, this article offers victim-survivor led understandings of what is needed to ensure the new paid DFV leave provisions are introduced and embedded effectively across Australian workplaces. It centres the experiences of victim-survivors by drawing on the findings of a national survey and in-depth interviews conducted with over 300 Australian DFV victim-survivors. The findings are relevant to current policy and practice debates across Australia.